2018
DOI: 10.1097/ico.0000000000001469
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye Assessment in Patients With Vitiligo

Abstract: This study showed that vitiligo is associated with tear hyperosmolarity and tear film dysfunction. Patients with vitiligo with periocular involvement may be more prone to dry eye than those without ocular involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…The association between vitiligo and dry eye was demonstrated in certain case-control studies, and our study further confirmed this association [24-26, 28, 29, 31]. According to the Tear Film and Ocular Surface Society (TFOS) Dry Eye Workshop (DEWS) II Diagnostic criteria, the diagnosis of dry eye disease consists of dry eye-related symptoms along with one of the homeostasis markers (TBUT, osmolality, and ocular surface staining) [43].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The association between vitiligo and dry eye was demonstrated in certain case-control studies, and our study further confirmed this association [24-26, 28, 29, 31]. According to the Tear Film and Ocular Surface Society (TFOS) Dry Eye Workshop (DEWS) II Diagnostic criteria, the diagnosis of dry eye disease consists of dry eye-related symptoms along with one of the homeostasis markers (TBUT, osmolality, and ocular surface staining) [43].…”
Section: Discussionsupporting
confidence: 87%
“…According to the Tear Film and Ocular Surface Society (TFOS) Dry Eye Workshop (DEWS) II Diagnostic criteria, the diagnosis of dry eye disease consists of dry eye-related symptoms along with one of the homeostasis markers (TBUT, osmolality, and ocular surface staining) [43]. Four out of the six included studies evaluated ocular surface staining, but only two of them performed with the Oxford scale, which showed no significant differences among patients with vitiligo and control [29, 31]. Due to the paucity of evidence, the ocular staining test was not further analyzed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our work supports the fact that periocular skin involvement in vitiligo patients is not a predictor of eye affection, a topic that has been studied with conflicting results in the past years. [19][20][21] Our data demonstrate a significantly lower CDVA in vitiligo patients when compared to age-and sex-matched controls. We could find two studies with ophthalmic assessment of vitiligo patients that included visual acuity comparisons with controls, and in both studies, the results showed that the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 48%
“…Nevertheless, our work supports the fact that periocular skin involvement in vitiligo patients is not a predictor of eye affection, a topic that has been studied with conflicting results in the past years. 19 21 …”
Section: Discussionmentioning
confidence: 99%
“…A study by Dogan et al 17 showed higher OSDI score, shorter TBUT, and shorter Schirmer test distance in vitiligo patients but the results were not statistically significant. Recently, Erdur et al 18 evaluated ocular surface and tear film parameters in vitiligo patients with and without periocular involvement and compared them with controls. They showed that patients with vitiligo had higher OSDI score, lower TBUT, and higher tear osmolality, but there was no significant difference in Schirmer test and ocular surface staining between the groups.…”
Section: Discussionmentioning
confidence: 99%